2007
DOI: 10.1016/j.vaccine.2006.12.045
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of a DNA vaccine containing inserted and replicated regions of the E7 gene for treatment of HPV-16 induced tumors

Abstract: A majority of cervical cancers are associated with HPV-16. A DNA vaccine (E7IR) was designed for prophylactic and therapeutic treatment of HPV-16+ tumors containing two repeats of the E7 gene to inactivate transformation and duplicate available epitopes. Mice were vaccinated then tumor challenged, or challenged and then immunized and monitored for tumor volume and survival. Splenocytes were utilized for in vivo CTL assays. The E7IR vaccine demonstrated decreased tumor volume and enhanced survival in prophylact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…The treatment of well-established tumors is a considerable challenge, and several groups have reported therapeutic activity with CIN-cervical cancer candidate vaccines [33], [34], [35], [36]. Only a few authors have reported regressions of tumors above 0.5 cm 3 [20], [37], in addition to efficacy against two inoculations (re-challenge), as we observed in our study.…”
Section: Discussionsupporting
confidence: 79%
“…The treatment of well-established tumors is a considerable challenge, and several groups have reported therapeutic activity with CIN-cervical cancer candidate vaccines [33], [34], [35], [36]. Only a few authors have reported regressions of tumors above 0.5 cm 3 [20], [37], in addition to efficacy against two inoculations (re-challenge), as we observed in our study.…”
Section: Discussionsupporting
confidence: 79%
“…Furthermore, mutation at E6 positions 63 or 106 has been shown to destroy several HPV-16 E6 functions, preventing the mutated E6 protein from immortalizing human epithelial cells [113,114]. Additional strategies to alleviate concerns for oncogenicity include employment of a shuffled E7 molecule, in which sequences encoding regions of the E7 protein were rearranged and certain sequences were duplicated to maintain all possible T-cell epitopes [100,115,116]. …”
Section: Therapeutic Hpv Dna Vaccine Clinical Trialsmentioning
confidence: 99%
“…In this approach, the native HPV16 E7 protein was split into 3 arbitrary regions designated as a, b and c; and all 3 regions, a, b and c were replicated to enhance expression This approach resulted in enhanced immunity as evidenced by the ability to prevent tumor formation and therapeutically treat existing tumors in C57BL/6 mice. 78 …”
Section: Dna Vector-based Therapiesmentioning
confidence: 99%